Risk of fire in heavy vehicles in steep road-tunnels - Nævestad, Tor-Olav; Høye, Alena Katharina; Blom, Jenny; Egner, Lars Even (Frontiers in Built Environment, 2025)
The present study examines the relationship between steep grades in road tunnels and the risk of heavy vehicle fires. The results show that fire risk in road tunnels increases with increasing maximum grade and with increasing length of steep grades. At grades above 7 percent, fire risk increases far more than at other grades, and 7 percent can be regarded as a “breakpoint” of increasing fire risk, especially among heavy vehicles. Subsea tunnels have far higher fire risk than other tunnels, mainly because they have both long and steep grades. The four most fire-prone subsea tunnels have grades over 7 percent that are more than 5 km long. These are the tunnels Oslofjord, Eiksund, Bømlafjord, and Byfjord. Most heavy vehicle fires in tunnels are caused by technical problems, mostly related to the engine. Overheating of the engine is often related to prolonged driving with a retarder downhill, followed by prolonged uphill driving. This pattern is typical in subsea tunnels. Overheating of engines is also often related to poor vehicle maintenance and insufficient vehicle inspections. To reduce heavy vehicle fire risk in tunnels, the most effective measure would be not to build tunnels with long steep grades (or to ban trucks from such tunnels). Other relevant measures to reduce vehicle fire risk include improved vehicle maintenance and inspections, as well as automatic fire extinguishing technology. Improved tunnel fire management, such as early detection and evacuation strategies, can contribute to avoid the most serious consequences. The introduction of new energy carries in the truck fleet, such as electric and hydrogen trucks, will affect both fire risk and fire management for heavy vehicles.